Variability of the air temperature and atmospheric precipitation in the high-mountain positions of the Low and High Tatras in winter - OSTROŽLÍK, Marian (Contributions to Geophysics and Geodesy, 2010)
On the basis of the fifty three-year time series of air temperature and precipitationin three levels of the atmospheric layer the seasonal variability of air temperatureand precipitation in the Low and High Tatras regions are studied. Measurements ofthe air temperature and precipitation at the meteorological observatories Lomnick´y štít,Skalnaté Pleso and Chopok during the 1955–2007 period were used to analyse the timeseries in winter season, and compared with the corresponding results from the normalperiod 1961–1990. By processing of the extensive experimental material many statisticalcharacteristics of the precipitation in the Low and High Tatra Mts were obtained.